2016
DOI: 10.1371/journal.pone.0163125
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Stability in FFPE Tissue Samples: Dependence on GC Content

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs responsible for fine-tuning of gene expression at post-transcriptional level. The alterations in miRNA expression levels profoundly affect human health and often lead to the development of severe diseases. Currently, high throughput analyses, such as microarray and deep sequencing, are performed in order to identify miRNA biomarkers, using archival patient tissue samples. MiRNAs are more robust than longer RNAs, and resistant to extreme temperatures, pH, and formali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 38 publications
(35 reference statements)
1
40
0
Order By: Relevance
“…Importantly, the inter-protocol similarities for matched samples tended to be higher than what was observed among different samples within either protocol. Of note, the low proportion of miRNA reads in both extraction protocols (Fig 4A) is likely due to degradation of miRNAs in FFPE RNA as reported previously [27]. Taken together, these data indicate that the FormaPure protocol yields adequate miRNA for library sequencing of reasonable diversity and quality.…”
Section: Resultssupporting
confidence: 80%
“…Importantly, the inter-protocol similarities for matched samples tended to be higher than what was observed among different samples within either protocol. Of note, the low proportion of miRNA reads in both extraction protocols (Fig 4A) is likely due to degradation of miRNAs in FFPE RNA as reported previously [27]. Taken together, these data indicate that the FormaPure protocol yields adequate miRNA for library sequencing of reasonable diversity and quality.…”
Section: Resultssupporting
confidence: 80%
“…For example, the presence of lithium-heparin as anticoagulants, and mechanical disturbances such as; the shaking for plasma isolation results in degradation of miRNAs (Glinge et al, 2017). In recent years, Kakimoto et al, (2016) have demonstrated that the miRNA stability is also depended on the GC content in their sequence, by which the miRNAs containing a GC content of less than 40% are more degraded than those of GC-rich miRNAs. These evidences may imply that storage of whole blood, serum, and in particularly plasma, may not be a proper source for miRNA determination.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 But, miRNA degradation does appear to vary between specific miRNAs with %GC being implicated, suggesting biases in FFPE-derived data. 25 Additionally, RNA quality is often an issue for FFPE tissue due to cross-linking. As well, devitalization times, times to fixation, or postmortem intervals (for autopsy-derived tissues), diminish the quality of the RNA before formalin fixation and storage has even begun for human tissues.…”
Section: Discussionmentioning
confidence: 99%